SOME PECULIAR DIFFERENCES OF BUSINESS IDIOM TRANSLATION (Mokslo taikomieji tyrimai / Applied Research, 2016)
Idioms are widely used and important part of the English language. They are considered to be one of the most peculiar elements of the language because of their structure and usage. When the text is being translated from a source language into a target language it goes through some changes. By means of translation tools the meaning of an idiom is conveyed. The utmost task for a translator is to detect the idiom or the allusion to it. Following the golden rules by Baker a translator in the process cannot change word order of the idiom, cannot drop a single word from it, cannot add a new word to it, cannot replace one word with another and change idiom’s grammatical structure. The research studies the main strategies used by translators translating the transparent, semi-transparent and opaque business idioms. For translators, in order to recognize idioms in the text and interpret them correctly, it is important to have at least basic knowledge of what idiom is, what its main features are and what kind of changes can be done during the process of translation. The classification based on the semantic principle was presented. The idiom under translation undergoes changes which are known as translation transformations, namely, transposition, substitution, addition and omission. For the present analysis one hundred of business idioms were collected from The Oxford Dictionary of Idioms 2004 and Dictionary of Idioms/ Anglų kalbos frazeologijos žodynas 2010. The main translation strategies used in translations and their semantic match of the lexical items in the target language were detected during the comparative analysis. The translation strategies and versions were compared. The research disclosed that Lithuanian translators as well as Lithuanian business text authors avoid idioms in business text and paraphrase them even when the Lithuanian idiomatic equivalent is a straightforward translation solution. Even 57 percent of all possible idiomatic equivalents in the target language were translated using the strategy of paraphrase.